Synthesis of bis(indolyl)methanes Catalyzed by Triethylborane - Pablo Garcia Merinos, J.; Lopez Ruiz, Heraclio; Lopez, Yliana; Rojas Lima, Susana (Letters in Organic Chemistry, 2015)
Triethylborane (TEB) was found to be a mild, efficient, and acid catalyst in electrophilic substitution reaction of indoles with aldehydes compounds to afford the corresponding bis(indolyl)methanes. Vibrindole A (5) and bis(indolyl)methanes derivatives 16 and 18 were synthesized using this methodology. Compound 16 is an intermediary in the synthesis of the natural bisindoles arsindoline B (2) and streptindole (6). The structure of vibrindole A (5) was unequivocally confirmed by a single crystal X-ray diffraction analysis.
Keywords: indole